Muscular Grip Strength Estimates of the U.S. Population From the National Health and Nutrition Examination Survey 2011–2012. Issue 3 (March 2016) - Perna, Frank M.; Coa, Kisha; Troiano, Richard P.; Lawman, Hannah G.; Wang, Chia-Yih; Li, Yan; Moser, Richard P.; Ciccolo, Joseph T.; Comstock, Brett A.; Kraemer, William J.
Abstract : Abstract: Perna, FM, Coa, K, Troiano, RP, Lawman, HG, Wang, C-Y, Li, Y, Moser, RP, Ciccolo, JT, Comstock, BA, and Kraemer, WJ. Muscular grip strength estimates of the U.S. population from the National Health and Nutrition Examination Survey 2011–12. J Strength Cond Res 30(3): 867–874, 2016—The purposes of this study were to use the National Health and Nutrition Examination Study (2011–12) data to determine nationally representative combined handgrip strength ranges and percentile information by sex and age group, examine trends in strength across age by sex, and to determine the relative proportion of children and adults falling into established health benefit zones (HBZ). Results indicate that mean strength was greater among men than women and increased linearly for children and in a quadratic fashion among adults for both sexes. Grip strength peaked in the 30- to 39-year age group for both men (216.4 lbs) and women (136.5 lbs) with subsequent age groups showing gradual decline, p < 0.0001. Relative and absolute increases in grip strength were greater for men than for women, but relative decrease from peak strength was less among women than men. Although absolute strength was greater among men than women, HBZ data indicated that a higher percentage of men than women overall and at each age group fell into the needs improvement zone, with differences particularly pronounced during adolescence and older adulthood. These data provide the first nationally representative population estimates of combined handgrip strength and percentile information from childhood through senescence and suggest consideration of HBZ information in conjunction with grip strength to improve surveillance data interpretation and intervention planning.